Late effects of 1H irradiation on hippocampal physiology. (May 2018) - Kiffer, Frederico; Howe, Alexis K.; Carr, Hannah; Wang, Jing; Alexander, Tyler; Anderson, Julie E.; Groves, Thomas; Seawright, John W.; Sridharan, Vijayalakshmi; Carter, Gwendolyn; Boerma, Marjan; Allen, Antiño R.
Abstract: NASA's Missions to Mars and beyond will expose flight crews to potentially dangerous levels of charged-particle radiation. Of all charged nuclei, 1 H is the most abundant charged particle in both the galactic cosmic ray (GCR) and solar particle event (SPE) spectra. There are currently no functional spacecraft shielding materials that are able to mitigate the charged-particle radiation encountered in space. Recent studies have demonstrated cognitive injuries due to high-dose 1 H exposures in rodents. Our study investigated the effects of 1 H irradiation on neuronal morphology in the hippocampus of adult male mice. 6-month-old mice received whole-body exposure to 1 H at 0.5 and 1 Gy (150 MeV/n; 0.35–0.55 Gy/min) at NASA's Space Radiation Laboratory in Upton, NY. At 9-months post-irradiation, we tested each animal's open-field exploratory performance. After sacrifice, we dissected the brains along the midsagittal plane, and then either fixed or dissected further and snap-froze them. Our data showed that exposure to 0.5 Gy or 1 Gy 1 H significantly increased animals' anxiety behavior in open-field testing. Our micromorphometric analyses revealed significant decreases in mushroom spine density and dendrite morphology in the Dentate Gyrus, Cornu Ammonis 3 and 1 of the hippocampus, and lowered expression of synaptic markers. Our data suggest 1 H radiation significantly increased exploration anxiety and modulated the dendritic spine and dendrite morphology of hippocampal neurons at a dose of 0.5 or 1 Gy.